Analysis the Composition of Hydraulic Radial Force on Centrifugal Pump Impeller: A Data-Centric Approach Based on CFD Datasets - Hehui Zhang; Kang Li; Ting Liu; Yichu Liu; Jianxin Hu; Qingsong Zuo; Liangxing Jiang (Applied Sciences)
Centrifugal pumps are essential in various industries, where their operational stability and efficiency are crucial. This study aims to analyze the composition and variation characteristics of the hydraulic radial force on the impeller using a data-centric approach based on computational fluid dynamics (CFD) datasets, providing guidance for optimizing impeller design. A high-precision CFD simulation on a six-blade end-suction centrifugal pump generated a comprehensive hydraulic load dataset. Data analysis methods included exploratory data analysis (EDA) to uncover patterns and trigonometric function fitting to model force variations accurately. Results revealed that the hydraulic radial force exhibits periodic behavior with a dominant blade passing frequency (BPF), showing minimal fluctuations at the rated flow rate and increased fluctuations as flow deviates. Each blade’s force could be approximated by sine curves with equal amplitudes and frequencies but successive phase changes, achieving high fitting quality (R2 ≥ 0.96). The force on the impeller can be decomposed into the contributions of each blade, with symmetric blades canceling out the main harmonics, leaving only constant terms and residuals. This study provides insights into force suppression mechanisms, enhancing pump stability and efficiency, and offers a robust framework for future research on fluid–structure interactions and pump design.